Interdental Fricative Substitution in Spontaneous Indonesian-Accented English: Acoustic Evidence from Podcast Speech - Arjuna Satria Dewa Bagaskara; Bintang Dja'far Maulana; Abdus Salim (Journal of English Language Teaching and English Linguistics, 2026)
Indonesian speakers of English consistently face difficulty producing the interdental fricatives /θ/ and /ð/, two sounds absent from the Indonesian consonant inventory, yet existing research has relied almost exclusively on controlled elicitation tasks that may not reflect how these sounds are realized in natural communicative settings. This study examined the phonetic realization of /θ/ and /ð/ in the spontaneous English speech of an Indonesian public figure, with the primary objective of determining whether acoustic evidence from unscripted digital media speech is consistent with the L1 phonological interference patterns previously reported in task-based studies. A descriptive qualitative design was adopted, with data drawn from a single podcast episode in which the subject produced English speech without scripting and without awareness of phonetic observation. All English utterances containing /θ/ or /ð/ were identified, timestamped, and submitted to acoustic analysis using Praat spectrographic software, with reference pronunciations from the Cambridge English Pronouncing Dictionary serving as the baseline. Twenty-four tokens were analyzed. Every instance of /θ/ was realized as the voiceless alveolar stop [t] and every instance of /ð/ as the voiced alveolar stop [d], yielding a one-hundred-percent substitution rate with no token approximating the interdental target. Spectrographic comparison confirmed the complete absence of fricative energy across all tokens. These findings demonstrate that L1 phonological interference at the interdental fricative site remains categorical and acoustically robust in spontaneous speech, independent of the speaker’s level of public communicative experience, extending prior evidence beyond the controlled task paradigm into naturalistic digital media discourse.